2016
DOI: 10.1128/jvi.00708-16
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of cis and trans Requirements for DNA Replication at the Right-End Hairpin of the Human Bocavirus 1 Genome

Abstract: Parvoviruses are single-stranded DNA viruses that use the palindromic structures at the ends of the viral genome for their replication. The mechanism of parvovirus replication has been studied mostly in the dependoparvovirus adeno-associated virus 2 (AAV2) and the protoparvovirus minute virus of mice (MVM). Here, we used human bocavirus 1 (HBoV1) to understand the replication mechanism of bocaparvovirus. HBoV1 is pathogenic to humans, causing acute respiratory tract infections, especially in young children und… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
49
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 35 publications
(55 citation statements)
references
References 64 publications
2
49
0
Order By: Relevance
“…We previously found that replication of the duplex HBoV1 genome in HEK293 cells requires the presence of a replication origin (Ori) within the REH and the 3= end noncoding region (NCR), as well as the HBoV1 NS1 and NP1 proteins (33). In the current study, we showed that the 3= NCR produces a small nonpolyadenylated RNA of 140 nucleotides (nt) from an intragenic RNA polymerase III (Pol III) promoter.…”
mentioning
confidence: 72%
See 2 more Smart Citations
“…We previously found that replication of the duplex HBoV1 genome in HEK293 cells requires the presence of a replication origin (Ori) within the REH and the 3= end noncoding region (NCR), as well as the HBoV1 NS1 and NP1 proteins (33). In the current study, we showed that the 3= NCR produces a small nonpolyadenylated RNA of 140 nucleotides (nt) from an intragenic RNA polymerase III (Pol III) promoter.…”
mentioning
confidence: 72%
“…Previously, we found that the presence of the HBoV1 3= NCR (nt 5221 to 5291) in cis is critical to viral DNA replication (33). Since the HBoV1 3= NCR is encompassed by BocaSR, we hypothesized that BocaSR is involved in replication of the HBoV1 DNA.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…It is 219 amino acids in length and shares only 46% identity and 62% similarity with the 185-amino-acid MVC protein (7). HBoV1 NP1 has been shown to be required for virus replication and is localized to viral replication centers (24). In certain contexts, it has been shown to interact with interferon regulatory factor 3 (IRF3) and thereby suppress interferon beta (25).…”
mentioning
confidence: 99%
“…The distance between (pA)d and (pA)d2 is 274 nt and affects polyadenylation efficiency at (pA)d2. This 3′ noncoding region (NCR) of HBoV has been predicted to form two conserved hairpin structures and plays an important part in the replication of bocaviruses (3941). The 3′ NCR could function as a binding site for miRNAs or be involved in the production of noncoding RNAs to regulate protein expression (42, 43).…”
Section: Discussionmentioning
confidence: 99%